Spatiotemporal Tuning of the Facilitation of Biological Motion Perception by Concurrent Motor Execution - Christensen, Andrea (J Neurosci, 2011)
The execution of motor behavior influences concurrent visual action observation and especially the perception of biological motion. The neural mechanisms underlying this interaction between perception and motor execution are not exactly known. In addition, the available experimental evidence is partially inconsistent because previous studies have reported facilitation as well as impairments of action perception by concurrent execution. Exploiting a novel virtual reality paradigm, we investigated the spatiotemporal tuning of the influence of motor execution on the perception of biological motion within a signal-detection task. Human observers were presented with point-light stimuli that were controlled by their own movements. Participants had to detect a point-light arm in a scrambled mask, either while executing waving movements or without concurrent motor execution (baseline). The temporal and spatial coherence between the observed and executed movements was parametrically varied. We found a systematic tuning of the facilitatory versus inhibitory influences of motor execution on biological motion detection with respect to the temporal and the spatial congruency between observed and executed movements. Specifically, we found a gradual transition between facilitatory and inhibitory interactions for decreasing temporal synchrony and spatial congruency. This result provides evidence for a spatiotemporally highly selective coupling between dynamic motor representations and neural structures involved in the visual processing of biological motion. In addition, our study offers a unifying explanation that reconciles contradicting results about modulatory effects of motor execution on biological motion perception in previous studies.